1991
DOI: 10.1111/j.1600-065x.1991.tb00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Immunity: A T‐Cell‐Independent Pathway of Macrophage Activation, Defined in the scid Mouse

Abstract: NTRODUCTIONIn this review we summarize our studies on macrophage activation in mice with the scid mutation. Such mice exhibit, to a remarkable extent, a cellular system capable of activating macrophages. This pathway of macrophage activation defmes the cellular immune system operating presumably in its most primitive form without the modulation of B or T cells, i.e., without adaptive immunity. This T cell-independent mechanism of macrophage activation constitutes an important line of defense and protection aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
156
0
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(163 citation statements)
references
References 68 publications
4
156
0
3
Order By: Relevance
“…The ability of TCR␣°mice to control primary L. monocytogenes infection is consistent with the previously recognized capacity of TCR␥␦ and NK cells to participate in innate immunity against this pathogen (3,6,10). No difference in the bacterial burden or early survival was observed among wild-type, TCR␣°, and TCR␣°V␣14Tg mice following enteric L. monocytogenes infection.…”
Section: Discussionsupporting
confidence: 87%
“…The ability of TCR␣°mice to control primary L. monocytogenes infection is consistent with the previously recognized capacity of TCR␥␦ and NK cells to participate in innate immunity against this pathogen (3,6,10). No difference in the bacterial burden or early survival was observed among wild-type, TCR␣°, and TCR␣°V␣14Tg mice following enteric L. monocytogenes infection.…”
Section: Discussionsupporting
confidence: 87%
“…g/d T cells segregate into two populations on the basis of NK1.1 surface expression and NK1.1 1 subsets have a higher potential to secrete IFN-g than their NK1.1 À counterparts [22]. Because a majority of g/d T cells appearing in the liver after a-GalCer treatment expressed NK1.1, NK1.1 1 rather than NK1.1 À , g/d T cells are probably responsible for the elimination of L. monocytogenes.NK1.1 1 cells had been considered to play a pivotal role in protection against L. monocytogenes infection, because they produce IFN-g immediately after infection [79][80][81][82] and because severe combined immunodeficient mice control listeriosis effectively in the beginning [83]. However, we found that resistance of mice against L. monocytogenes was enhanced by NK-cell depletion, arguing against a protective role of NK cells in listeriosis.…”
mentioning
confidence: 73%
“…CD4 and CD8 T cells are important for conferring sterilizing immunity since SCID mice develop a chronic infection [3,4]. While both CD4 and CD8 T cells contribute to protective immunity, in vivo depletion and adoptive transfer studies have clearly demonstrated that memory CD8 T cells are the most effective T cell subset capable of mediating protection [55,56].…”
Section: Cd4 and Cd8 T Cell Responsesmentioning
confidence: 99%